Novel findings regarding treatment obesity and weight-related comorbidities – the systemic literature review - Urbańska, Karina; Popiela, Dariusz; Stojak, Łukasz; Kwiatkowski, Filip; Grego, Katarzyna; Grego, Mateusz; Baczewski, Mateusz; Czyż, Witold (Quality in Sport, 2025)
Obesity and overweight are a growing health problem worldwide and are recognized as risk factors for many health complications and increased mortality. Therefore, it is necessary to take decisive action to fight the obesity epidemic to avoid significant costs associated with the treatment of diseases related to excess body weight. Recent years have brought many new drugs that are very effective in obesity treatment and even more are in clinical trials. This review aims to synthesize the literature regarding new drugs and their effectiveness in treating obesity and their impact on related diseases. A systematic search was conducted across multiple sources, including PubMed, Google Scholar, ResearchGate, ClinicalTrials, FDA, and EMA databases. Currently, the most effective medications seem to be tirzepatide and retatrutide, which might provide more than 15% weight loss. However, other drugs show promising results in improving glycemic control, cardiovascular health (semaglutide and tirzepatide), lipid levels, the regression of fibrosis (survodutide), or alleviating OBS symptoms (tirzepatide). Tailored therapy combining both medication’s weight-reducing capacity and the patient’s comorbidities provides the most beneficial effects.